2011
DOI: 10.1038/onc.2010.593
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor activation enhances SK3 channels- and cystein cathepsin-dependent cancer cells invasiveness

Abstract: ATP-gated P2X 7 receptors (P2X 7 R) are unusual plasma membrane ion channels that have been extensively studied in immune cells. More recently, P2X 7 R have been described as potential cancer cell biomarkers. However, mechanistic links between P2X 7 R and cancer cell processes are unknown. Here, we show, in the highly aggressive human breast cancer cell line MDA-MB-435s, that P2X 7 receptor is highly expressed and fully functional. Its activation is responsible for the extension of neurite-like cellular prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
177
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(194 citation statements)
references
References 43 publications
10
177
0
1
Order By: Relevance
“…On the contrary, P2X7 activation may support cell proliferation, tumour growth or metastatic activity [34,35]. Thus, for instance in human breast cancer cells or in a rat brain glioblastoma model, inhibition of P2X7 has been suggested as potential therapeutic strategy to slow the progression of tumours [36,37]. Therefore, depending on the cellular context, P2X7 might limit or promote the proliferation of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, P2X7 activation may support cell proliferation, tumour growth or metastatic activity [34,35]. Thus, for instance in human breast cancer cells or in a rat brain glioblastoma model, inhibition of P2X7 has been suggested as potential therapeutic strategy to slow the progression of tumours [36,37]. Therefore, depending on the cellular context, P2X7 might limit or promote the proliferation of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that P2X7 receptor activation enhances invasiveness through a mechanism involving Ca 2+ -activated SK3 K + -channel activity in the mammary carcinoma cell line MDA-MB-435 s [65]. In addition, P2X7 receptor activation in T47D breast cancer cells induces an increase in cell invasiveness associated with the expression of EMT markers, such as E-cadherin and MMP-13, via the AKT pathway [66].…”
Section: Adora2amentioning
confidence: 99%
“…Various cancer cells over-express P2X7 receptors [84][85][86][87] that regulate their motility (e.g., C6 glioma cells [88] and breast cancer cells [89]). ATP enhances the migration of TGFβ1-treated A549 lung cancer cells, although the precise receptor responsible for this effect has not yet been identified [90].…”
Section: Cancer Cellsmentioning
confidence: 99%